AB0184 Chromosomal aberrations are associated with disease severity in a mouse model of bleomycin-induced scleroderma. (15th June 2017) - Luisetto, R; Beggio, M; Scanu, A; Oliveira, F Leite de; Pigatto, E; Peruffo, A; Zanatta, E; Oliviero, F; Sfriso, P; Punzi, L; Cozzi, F
Abstract : Background: Scleroderma (SSc) is a connective tissue disease characterized by immunomediated inflammation and fibrosis. The presence of autoantibodies against chromosome associate proteins, such as anti-centromere proteins and anti-topoisomerase I, was observed in SSc patients, however genotoxic events have never been evaluated (2). Objectives: To assess the presence of aneuploidia, micronuclei (MN) and other chromosomal aberrations in peripheral lymphocytes in a bleomycin (BLM)-induced scleroderma mouse model. Methods: BALB/c mice (n=20 per condition) were injected subcutaneously daily with BLM 2mg/kg or PBS (control) for 14 days. Urine was collected weekly and proteinuria was measured. At day 15 mice were sacrificed and organs harvested for histological analysis. The MN assay was performed on cultured peripheral lymphocytes isolated from mice spleens. Cells were treated with cytochalasin B (10 μg/ml) for 24 h and a minimum of 1000 binucleated cells/mouse were scored following the criteria of Fenech (1). The antikinetochore (CREST) staining was used to determine the origin of MN observed. Results: In BLM treated mice was observed huge perivascular lung fibrosis and significant skin involvement. 17 out of 20 mice developed acute renal involvement with mean proteinuria levels of 730±48 mg/dl. In comparison with the control mice, a significant increase in MN number was observed in BLM treated mice (57, 8±4, 4 vs 6, 3±0, 6, p<0.05). CREST staining was higher in MN derived from BLM treated mice (16, 4±1, 1 vs 3, 7±0, 7, p<0, 025), indicating that in this group lymphocyte MN arised mainly from lagging chromosomes. In addition, an increased frequency of ring chromosome was observed in mice with greater skin fibrosis and renal involvement.A correlation between the presence of CREST stained MN and disease severity parameters as renal failure, lung and skin fibrosis was observed (respectively R=0, 4095; R=0, 7507 and R=0, 9471). Conclusions: This study provides experimental evidence that significant chromosomal aberrations seem to be related to the severity of disease in a mouse model of SSc. Further investigations on lymphocytes obtained from SSc patients could be matched with results observed in mouse model to confirm the relationship between severity of the disease and chromosomal abnormalities. References: Fenech M. Cytokinesis-block micronucleus cytome assay. Nature Protocols 2006, 2(5): 1084–1199. Korman BD and Criswell LA. Recent advances in the genetics of systemic sclerosis: toward biological and clinical significance. Curr Rheumatol Rep 2015, 17(3): 21–34. Disclosure of Interest: None declared